An azido-bridged [FeII4] grid-like molecule showing spin crossover behaviour. Issue 40 (23rd September 2021) - Guo, Zhilin; You, Maolin; Deng, Yi-Fei; Liu, Qiang; Meng, Yin-Shan; Pikramenou, Zoe; Zhang, Yuan-Zhu
Abstract : The first azido-bridged spin crossover complex with a [Fe II 4] grid core ( T 1/2 = 230 K) was successfully engineered through supramolecular coordination assembly, and it also exhibited a clear synergy between the SCO event and luminescence. Abstract : The supramolecular self-assembly synthetic strategy provides a valid tool to obtain polynuclear Fe(ii ) complexes having effective communication between the metal centres and distinct spin crossover behaviour. Despite the great success in constructing various magnetic molecules, progress has not been made in SCO complexes based on azido bridges. In this article, the coordination-driven supramolecular assembly based on 3, 6-substituted pyridazine and azide is presented to afford two Fe(ii ) grid-like complexes: [(L)4 FeII4(N3 )4 ][BPh4 ]4 ·sol (1, L = 3, 6-bis(3, 5-dimethyl-1 H -pyrazol-1-yl)pyridazine and 2, L = 3, 6-di(pyridin-2-yl)pyridazine). The substitution of pyridinyl groups in 2 instead of pyrazolyl ones in 1 led to the only example exhibiting spin-crossover behaviour ( T 1/2 = 230 K) among the azido-bridged complexes. In addition, a temperature-dependent photoluminescence study of 2 demonstrates a visible synergetic effect between the SCO event and the luminescence.